(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article provides data on the study of biochemical parameters in 48 women with pelvioperitonitis (PP). All patients, depending on the treatment performed, were divided into 3 groups: group 1 (n=25) received traditional conservative therapy; Group 2 (n=23) received long-term pelvic microcatheter therapy (LPMT) into the pelvic cavity. When treating LPMT, we used sulperazone (Pfizer, USA) 1 g/day for 6 - 8 days (course of treatment), as well as additionally metronidazole 0.5% - 10 ml. When treating patients with PP, their leukocytes show a disturbance in NO metabolism, inhibition of ND activity, and an increase in the rate of the NR enzymatic reaction. An important factor in reducing the expression of NO is the inhibition of ND activity and the intensification of the rate of the NR enzymatic reaction. Disturbance of the NO-ergic system in leukocytes is associated with an increase in the degree of EI in patients with PP. The inclusion of sulperazone and metronidazole in the treatment regimen using the LPMT method in patients with PP was more effective compared to the traditional method, since it improved both biochemical parameters and the results of treatment of patients.